Data of Project on Atmospheric Circulation and Material Cycle in the Antarctic, Part 2. : NOAA AVHRR Images received at Syowa Station, Antarctica in 1997 - Hirasawa, Naohiko; Yamanouchi, Takashi (National Institute of Polar Research, 2000)
P(論文) departmental bulletin paper